Pharmacognostic Identification and Specific Quality Parameters of Blue Porterweed (Stachytarpheta jameicensis) Leaf Extract from Enrekang Regency, South Sulawesi - amin, asni; Risda Waris; Noer Kurnia; Nur Fadilla (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
The leaves of Blue Porterweed (Stachytarpheta jamaicensis) are commonly found in Enrekang district and used as medicinal plants. Its pharmacological effects have been tested invitro and invivo. However, data on the quality of this extract is still unpublished. This study was conducted to identify the pharmacognostic and specific quality parameters of horse whip leaf extract from Enrekang district. The research method is laboratory experimental. Pharmacognostic identification was carried out by identifying plant morphology, macroscopic test of simplisia, and identification of chemical content by Thin Layer chromatography (TLC). The extract obtained from maceration using 70% ethanol and then determined its specific parameters including organoleptic tests, extract identity parameters, soluble extract content in certain solvents. The results of pharmacognostic identification that have been carried out show that horse whip is a shrub, 50 cm-1.2 m high, taproot, lanceolate leaf, serrated edges, pinnate leaf repetition and belongs to the Verbenaceae family, and the TLC results of the extract show the presence of alkaloid, phenol, and flavonoid compounds. The identity name of the extract is Stachytarpetae Folium Extractum, black brown in colour, thick extract texture, slightly bitter taste, and weak odour. Test results of water soluble extract content = 14.96% and ethanol soluble extract content = 15.23%. Conclusion: Data on specific quality parameters of blue porterweed leaf extract will be a reference for the manufacture of standardised herbal medicine.